Pengelolaan Manajemen Sumber Daya Manusia dalam Meningkatkan Kinerja Guru SMA Citra Madinatul Ilmi Kota Banjarbaru - Sri Bulkia; Orbawati Orbawati; Husnurrofiq Husnurrofiq; Periyadi Periyadi; Junaidi Junaidi; Abdurrahman Abdurrahman (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this community service is to help provide direction and counseling to the Principal, Vice Principal, Administrative Staff, and Teachers' Council of Citra Madinatul Ilmi Banjarbaru High School , regarding the introduction of elements of human resource management. Counseling in order to increase insight and knowledge for the Principal, Vice Principal, Administrative Staff, and Teachers' Council. The method of implementing this community service is carried out in several activities, namely the survey stage, namely socialization is carried out by compiling various things that will be conveyed during the community service activities that will be carried out which include: preparing the material to be provided, preparing the schedule for providing materials and surveying the community service location. The socialization stage, namely before the community service activities are carried out, a socialization stage is carried out, namely conducting a friendly meeting with the school to convey the intent and purpose of this community service. At this stage, cooperation is also established and the community service activity schedule is determined.